CENPs and Sweet Nucleosomes Face the FACT. Issue 9 (September 2016) - Murawska, Magdalena; Ladurner, Andreas G.
Abstract : Chaperones mediate vital interactions between histones and DNA during chromatin assembly and reorganization. Two recent studies reveal novel substrates for the essential and conserved histone chaperone FAcilitates Chromatin Transcription (FACT). Prendergast et al. show that FACT helps deposit important histone-fold proteins on centromeres. Raj et al. find that FACT preferentially binds O -GlcNAcylated nucleosomes, suggesting that FACT may contribute to nutrient-regulated cellular programs.